Upaya Peningkatan Mobilitas Fisik Pada Pasien Stroke Non Hemoragik - Wicaksono, Primadita; , Enita Dewi, S.Kep., Ns (2017)
BACKGROUND : Stroke or brain attack is a clinical syndrome that early onset of sudden, progressive, fast, in the form of focal neurological deficits and or global, lasting 24 hours or more, or directly cause death, and merely caused by circulatory disorders of the brain non-traumatic. Non-hemorrhagic stroke is defined as a set of clinical signs that developed by vascular causes. These symptoms lasted 24 hours or more generally occurs due to reduced blood flow to the brain, causing disability or death. According to WHO estimates, as many as 20.5 million people in the world have been infected jumlahtersebut stroke in 2011. Of the 5.5 million people had died. High blood pressure or hypertension donate 17.5 million cases of stroke in the world. Objective : To describe efforts to increase physical mobility in stroke patients nonhemoragik Methods : The descriptive method with case study approach in special chambers RS x February 11-13, 2017. The collection of data by observation, physical examination, medical records, interviews, documentary studies of journals and books. Results : The patient has not shown an increase in physical mobility after the action. Conclusion : The action Range Of Motion (ROM) and Interpretation baring effectively improve physical mobility. Suggestion: Measures ROM and over the rest may as inputs in independent nursing actions to improve physical mobility.